Postextractive Alveolar Ridge Preservation Using L-PRF: Clinical and Histological Evaluation - Serafini, Giorgio (Case Rep Dent, 2020)
Leukocyte- and platelet-rich fibrin (L-PRF) is an autologous platelet concentrate rich in growth factors and plasma proteins, obtained by centrifugation of patient whole blood, and widely used in oral surgery. This report describes a case of alveolar ridge preservation with L-PRF membranes. Postextractive alveolar healing was then assessed through a histologic and histomorphometric analysis. A patient requiring tooth extraction and subsequent implant rehabilitation was treated with simple extraction and socket filling with L-PRF membranes. Implant placement was performed at 3 months, and a bone biopsy was obtained for histomorphometric analysis. Histological examination of the grafted sites showed that the use of L-PRF could achieve good results in terms of bone dimension and quality and soft tissue healing. The results of this study support the use of L-PRF membranes to preserve hard and soft tissues after tooth extraction.